Legal Protection Of Artificial Intelligence Design Artworks In Indonesia - Maulana Malik Afif Nasuha; Mega Puspa Mandiri; Annisa Tya Zavira; Tina Marlina; Solichin Solichin (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In the midst of developments, many technologies are developing rapidly, one of which is artificial intelligence which was created to make human work easier. However, on the other side of the benefits for humans in using Artificial Intelligence technology, there is a problem that must be resolved in the future. One of them is a legal problem that is being faced all over the world. Even in Indonesia, several artists working in the field of design art still consider the use of Artificial Intelligence to violate copyright regulations. This is caused by the absence of strong regulations that specifically regulate Artificial Intelligence in Indonesia. Therefore, this research aims to see how moral responsibility is when the law makes actions that have a direct impact on society and how legal protection is for design art results that use artificial intelligence when linked to applicable regulations This research uses normative juridical research methods with a conceptual approach. The conceptual approach is based on the views and doctrines of various experts who have experienced developments in legal science.In Indonesia itself, there are no legal regulations that apply specifically to regulate Artificial Intelligence. In Law number 19 of 2016 concerning Information and electronic transactions, it is explained that Artificial Intelligence is categorized as a legal object, not a legal subject, but this does not rule out the possibility that Artificial Intelligence could become a legal subject. Meanwhile, Law no. 28 of 2014 concerning copyright explains that the person who can be held responsible before the law is the creator of the AI ​​or the service provider for using Artificial Intelligence and for the results of the design artwork not violating copyright while taking data on the design artwork taken from the property. another person has obtained a license or permit by the person concerned. Therefore, it is immediately necessary to enact special laws that regulate Artificial Intelligence and to overcome further undesirable things, society needs to pay attention to moral responsibilities in using Artificial Intelligence, such as understanding how to use this technology in an ethical, responsible manner. and know the limits and need to ensure that no party is harmed